ANALISIS EFEKTIVITAS PROGRAM MEMBERSHIP CARD DALAM MENCIPTAKAN LOYALITAS AFEKTIF KONSUMEN MATAHARI DEPARTMENT STORE DI SURABAYA - Maatita, Glenn Russell (Kajian Ilmiah Mahasiswa Manajemen, 2013)
The main objective of this study was to identify affective consumer loyalty can be built through the loyalty program. Implementation of loyalty programs are widely applied to companies engaged in retail business such as Matahari Department Store with membership card ownership called the "Matahari Club Card (MCC)". Variables in this study consists of independent variables and the dependent variable. The independent variable is the loyalty program membership card ownership, while the dependent variable in this study is composed of affective loyalty of consumer attitudes, consumer satisfaction, consumer trust, and consumer commitment. The quantitative analysis in this study using analysis of variance (ANOVA), validity testing, and reliability testing. The findings in this study is the ownership of a membership card have significant effect on consumer affective loyalty that consumer attitudes, consumer satisfaction, consumer trust, and consumer commitment. Another finding is the difference in affective loyalty between consumers owners and non-owner of membership card, which the Owner of MCC Beauty and MCC Premium have higher affective loyalty higher than Non-Owner of MCC, while there is not much different between Owner of MCC Regular and Non-Owner of MCC. It can be interpreted that the MCC Beauty and MCC Premium is a Matahari Department Store’s program that is effective in creating consumers affective loyalty.